Measuring the Costs and Coverage of SME and Entrepreneurship Policy: A Pioneering Study. (July 2014) - Lundström, Anders; Vikström, Peter; Fink, Matthias; Meuleman*, Miguel; Głodek, Paweł; Storey, David; Kroksgård, Andreas
This paper documents a methodology used to assess, for the first time, the costs to the taxpayer of small and medium enterprise (SME) and entrepreneurship policy in Sweden. It then uses that data to compare the resulting expenditure patterns with the focus of policy as expressed by experts. It finds important areas where the two diverge, implying a possible mismatch between expenditure priorities and political rhetoric. This approach is then extended beyond Sweden to include Poland, Austria, and the Flanders region of Belgium to demonstrate the application of the approach to other countries and regions.